Experimental Evidence on Adoption and Impact of the System of Rice Intensification. Issue 1 (4th July 2021) - Barrett, Christopher B.; Islam, Asad; Mohammad Malek, Abdul; Pakrashi, Debayan; Ruthbah, Ummul
Abstract : We report the results of a large‐scale, multi‐year experimental evaluation of the System of Rice Intensification (SRI), an innovation that first emerged in Madagascar in the 1980s and has now diffused to more than fifty countries. Using a randomized training saturation design with a pure control group, we find that greater cross‐sectional or intertemporal intensity of direct or indirect training exposure to SRI has a sizable, positive effect on Bangladeshi farmers' propensity to adopt (and not to disadopt) SRI. We find large, positive, and significant impacts of SRI training on rice yields and profits, as well as multiple household well‐being indicators, for both trained and untrained farmers in training villages. We also find high rates of disadoption, and clear indications of non‐random selection into technology adoption conditional on randomized exposure to training, such that adopters and non‐adopters within the same treatment arm experience similar outcomes. Rice yields, profits, and household well‐being outcomes do not, however, vary at the intensive margin with intensity of training exposure, a finding consistent with multi‐object learning models.